Creative Thinking and its Relationship to the Quality of Life for Physical Education Teachers in Najaf - Aqeel Yahya Hashim Abdulaziz1 , Noor Latif Abdul Zahra2 , Hayder Naji Habash Alshawi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This type of thinking is considered important for the individual and society, because of the creative outcome that is achieved as a result of the presence of individuals with the ability to be creative in various areas of life, if the individual has the appropriate environment for the growth of his creative thinking, which can be one of the reasons that play a role in assessing the quality of life for education studies Of sports in the province of Najaf, and the research aims to identify the level of reasoning thinking and the level of quality of life for female teachers of physical education affiliated to the director of education for the province of Najaf, and to identify the relationship between the level of creative thinking and the level of quality of life for teaching women Of sports in Najaf governorate, and the researchers assume that there is no correlation between the level of creative thinking and the level of quality of life among the teachers of physical education in the province of Najaf, the researchers used the descriptive method in the survey method and the correlations of its relevance to the nature of the research problem on the studies of physical education in the province of Najaf for the academic year 2019- 2020, and the number (35) female teachers belonging to the Directorate of Education in the province of Najaf and were chosen in a simple random manner. The researchers concluded that the level of creative thinking and the quality of life for physical education teachers in the middle level, and the existence of a significant correlation between creative thinking and quality of life, and the development of creative thinking was reflected in the quality of life for physical education teachers.